Global Mapping of Sustainability Accounting and Green Supply Chain Research: A Bibliometric Analysis - Arsy Annisa Asti; Royanti Sinaga (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2026)
This study addresses an underexplored research gap in the sustainability literature: despite the parallel growth of sustainability accounting (SA) and green supply chain management (GSCM) over the past two decades, their intellectual integration remains insufficiently mapped. Existing bibliometric reviews examine each domain in isolation, leaving the structural and thematic linkages between accounting-based sustainability measurement and supply chain-level environmental practices largely uncharted. This study fills this gap by conducting a comprehensive bibliometric analysis of 6,356 peer-reviewed journal articles indexed in Scopus (2005–2025) using VOSviewer. Beyond conventional bibliometric mapping, this study introduces a conceptual framework linking SA and GSCM through three bridging mechanisms: measurement, governance, and strategic alignment. The analysis covers publication trends, intellectual foundations (co-citation networks), thematic evolution (keyword co-occurrence and bibliographic coupling), and an overlay visualization of temporal keyword shifts. Findings reveal a post-2021 surge in publications, strong disciplinary anchoring in business, management, and environmental sciences, and the emergence of five integrated thematic clusters. A future research agenda is proposed across five emerging frontiers: AI for sustainability accounting, ESG analytics, blockchain-based sustainability reporting, green digital supply chains, and carbon accounting ecosystems. This study contributes conceptually by positioning SA as the measurement infrastructure of GSCM, theoretically by integrating institutional theory and resource-based view perspectives, and practically by offering implications for managers, policymakers, and researchers.